Developmental stages of fish blood flukes, Cardicola forsteri and Cardicola opisthorchis (Trematoda: Aporocotylidae), in their polychaete intermediate hosts collected at Pacific bluefin tuna culture sites in Japan. Issue 1 (February 2017) - Ogawa, Kazuo; Shirakashi, Sho; Tani, Kazuki; Shin, Sang Phil; Ishimaru, Katsuya; Honryo, Tomoki; Sugihara, Yukitaka; Uchida, Hiro'omi
Abstract: Farming of Pacific bluefin tuna (PBT), Thunnus orientalis, is a rapidly growing industry in Japan. Aporocotylid blood flukes of the genus Cardicola comprising C. orientalis, C . opisthorchis and C . forsteri are parasites of economic importance for PBT farming. Recently, terebellid polychaetes have been identified as the intermediate hosts for all these parasites. We collected infected polychaetes, Terebella sp., the intermediate host of C . opisthorchis, from ropes and floats attached to tuna cages in Tsushima, Nagasaki Prefecture, Japan. Also, Neoamphitrite vigintipes (formerly as Amphitrite sp. sensu Shirakashi et al., 2016), the intermediate host of C . forsteri, were collected from culture cages in Kushimoto, Wakayama Prefecture, Japan. The terebellid intermediate hosts harbored the sporocysts and cercariae in their body cavity. Developmental stages of these blood flukes were molecularly identified using species specific PCR primers. In this paper, we describe the cercaria and sporocyst stages of C . opisthorchis and C . forsteri and compare their morphological characteristics among three Cardicola blood flukes infecting PBT. We also discuss phylogenetic relations of the six genera of the terebellid intermediate hosts ( Artacama, Lanassa, Longicarpus, Terebella, Nicolea and Neoamphitrite ) of blood flukes infecting marine fishes, based on their morphological characters. Graphical abstract: Highlights: Sporocyst and cercaria of Cardicola opisthorchis are described. Sporocyst and cercaria of Cardicola forsteri are described. Phylogeny of the polychaete hosts of blood flukes of marine teleosts is discussed.